Epidemiology of Covid-19 in Yemen: A Descriptive Study - Alshaikhli, H; Al-Naggar, RA; Al-Maktari, L; Madram, S; Al-Rashidi, RR (International Journal of Life Science and Pharma Research, 2020)
In Yemen, the first COVID-19 confirmed case was reported on 10 April 2020. The World Health Organization representative in Yemen reported that approximately 65000 deaths and 49, 4000 will be hospitalized in Yemen if there are no protection measures at the right time. Therefore, the objective of this study is to identify the epidemiological characteristics of COVID-19 patients in Yemen. From May 20 to 31, 2020, the data were obtained from the National Center of Public Health Laboratories, Ministry of Health and population, Aden, Yemen. Confirmed cases are defined as polymerase chain reaction assay (PCR) positive. Cases included in this study are laboratory-positive cases. A retrospective study was used to determine the first 53 confirmed epidemiological characteristics of patients with COVID-19 in Yemen. This data includes the date of diagnosis, gender, age, governorates, and clinical symptoms. Data analyzed using SPSS V.22. A total number of 53 confirmed cases were obtained from the National Center of Public Health Laboratories, Ministry of Health and population, Aden, Yemen. The majority of the participants were male (72%), age less than 39 years (40%), and from Aden governorate (43%). The most typical symptoms reported among the participants were fever and cough (90%), followed by the sore throat (81%). The COVID-19 is common in Yemen among males, those less than 39 years old, and from Aden. This study’s findings may help guide the decision-makers, frontliners, and medical staff in the clinical management outbreak.
Keywords: COVID-19; Yemen; Epidemiology; Aden; Descriptive; Coronavirus